Real-time imaging of cell-surface proteins with antibody-based fluorogenic probes. Issue 40 (24th September 2021) - Wang, Wenchao; Zhang, Ying; Zhao, Hong; Zhuang, Xinlei; Wang, Haoting; He, Kaifeng; Xu, Wanting; Kang, Yu; Chen, Shuqing; Zeng, Su; Qian, Linghui
Abstract : A modular strategy to convert commercially available antibodies into fluorogenic probes has been developed, enabling selective recognition and wash-free imaging of endogenous membrane proteins. Abstract : Cell-surface proteins, working as key agents in various diseases, are the targets for around 66% of approved human drugs. A general strategy to selectively detect these proteins in a real-time manner is expected to facilitate the development of new drugs and medical diagnoses. Although brilliant successes were attained using small-molecule probes, they could cover a narrow range of targets due to the lack of suitable ligands and some of them suffer from selectivity issues. We report herein an antibody-based fluorogenic probe prepared via a two-step chemical modification under physiological conditions, to fulfill the selective recognition and wash-free imaging of membrane proteins, establishing a modular strategy with broad implications for biochemical research and for therapeutics.